Analysis of a Single Centre's Protocol of the Treatment of 5th Metatarsal Fractures. What Patients Need a Face-To-Face Fracture Clinic Review?. Issue 4 (November 2022) - Chapman, James; Choudhary, Zain A.; Gupta, Shubhi; Davies, Thomas; Airey, Grace L.; Mason, Lyndon W.
Category: Midfoot/Forefoot; Trauma Introduction/Purpose: 5th metatarsal fractures are a common injury attending foot and ankle clinics in the UK. Within our department, we established a protocol to reduce the burden on fracture clinic of 5th metatarsal fractures by limiting face-to-face consultations to Zone 2 and 3. We sought to investigate whether our practice was consistent and the ultimate patient destination. Methods: Patients were identified from our database. We included all 5th metatarsal fractures referred to our virtual fracture clinic with a confirmed 5th metatarsal fracture. Data was collected on virtual fracture clinic (VFC) outcomes including telephone review, clinic reviews and requirement of surgery. Plain AP radiographs were reviewed for fracture morphology. Fractures were defined as Zone 1.1, 1.2, 1.3, 2, 3, diaphyseal shaft (DS), distal metaphysis (DM) and head. A binary linear regression analysis model was used. All data was analysed using IBM SPSS v.27. Results: 1360 patients met the inclusion criteria (mean age of 48.1; range 16-95, sd=19.1). 430 (31.6%) were planned for face-to- face review, however following telephone review, 542 (39.9%) were sent appointments (p<.001 McNemar). On univariate analysis, only fractures in Zone 1.1 were associated with a plan to discharge from VFC (OR 2.851, p<.001), with Zone 3 fractures associated with a plan for face-face review (p<.001). Following telephone review, Zone 2 (OR 1.387, p=.034) and Zone 3 (OR 3.285, p<.001) fractures were the only fractures significantly associated attending a face-to-face clinic appointment, with Zones 1.1 (OR 0.573, p=.008) and 1.2 (OR 0.642, p=.033) negatively associated. Zone 3 fractures were the only fractures that retained significance for attending >1 appointment (OR 4.639, p>.001) and requiring surgery (OR 3.895, p=.037). Only 15 patients (1.1%) required surgery, with 9 being for non-union and 5 being acute operations in younger patients (median age = 34 vs 51). Conclusion: There was a significant increase in patients requiring face-face review after telephone conversation. In addition to Zone 3 injuries and Zone 2 injuries had also required face-face reviews following telephone consultation. Based on these results, all Zone 2 and 3 fractures should be considered for at least one face-to-face fracture clinic review. Operative management is rare and usually secondary to non-union.